The Impact of Norm- and Criterion-Referenced Grading Systems on Students’ Course-Related Expectations - Jingxuan Liu; Michelle Wong; Bridgette Hard (Journal of the Scholarship of Teaching and Learning)
The present study examined how information about different grading systems affects students’ course expectations, particularly in ways that may have downstream consequences for learning and other academic outcomes.   In an online experiment using a preregistered design, we prompted two samples of current and recent college students (N = 547) with a hypothetical course that adopted either a norm- or criterion-referenced grading system, two common grading policies in higher education. We then examined students’ expectations for their own course-related goals, perceptions, and behaviors. We found that, compared to criterion-referenced grading, norm-referenced grading led participants to expect higher performance-goal orientation, lower mastery-goal orientation, lower course self-efficacy, and fewer help-related behaviors. Norm-referenced grading also increased perceptions that the instructor believes intelligence to be nonuniversal and fixed (i.e., not malleable). Some effects of grading system were stronger for students from non-minoritized backgrounds and lacking prior experience with the assigned grading system. Although participants reported experiencing criterion-referenced grading more often in college, both grading policies were commonly experienced by participants. Our findings suggest that norm-referenced grading policies negatively impact student expectations. More broadly, these findings highlight the importance of grading policies in shaping students' course-related expectations.